An assessment of cash flow management: a case of Premier Tobacco Auction Floors - Mukandi, Melisa C. (Midlands State University, 2017)
Premier Tobacco Auction Floors is a newly established company in the Zimbabwean Tobacco Industry. The industry has high revenue generation because agriculture generally plays a big role in Zimbabwean economy. The Tobacco is sold between February and August and it is during this time that the company makes the bulk of its proceeds in a year .The company faces problems in handling and distributing this vast amount of cash and sometimes there is mismanagement of cash. By the time the tobacco selling season ends , the liabilities will be too unbearable for the low turnover offseason period .This mismanagement has resulted in high creditors figures ,loss of customers and necessary losses in lawsuits.